Analisis Pengaruh UI/UX dalam Aplikasi Livin By Mandiri : Dampaknya Terhadap Pengalaman dan Kepuasan Pengguna di Wilayah Kota Bandung - Sitanggang, Andri Sahata; Pramesti, Maritza Zahrin; Azzahra, Tiara Nirmala; Mumtazah, Iffah; Sitorus, Iin Eliwati (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Competition in the digital banking sector encourages banks to improve the quality of service through user-friendly, intuitive, and attractive mobile banking applications. However, there is still a mismatch between expectations and reality, where users face obstacles such as confusing icons, unresponsive features, and unattractive designs. This study aims to analyze the effect of Livin by Mandiri's UI/UX design on user satisfaction in Bandung City. The elements analyzed include visual aspects, navigation, performance, and the application's ability to adjust to user needs. This study uses a quantitative method with a questionnaire to 181 respondents who are Livin by Mandiri users. The results show that 91% of the respondents agree that quality of UI/UX greatly affects user satisfaction, especially in terms of appearance and ease of use. However, some respondents still complain about both aspects. These findings are expected to be input for Livin by Mandiri to improve digital services through UI/UX improvements for user satisfaction.